Using Bronfenbrenner’s ecological theory to understand community partnerships: A historical case study of one urban high school - Leonard, Jack (Urban Education, 2011)

Digital Gender Divide or Technologically Empowered Women in Developing Countries? A Typical Case of Lies, Damned Lies, and Statistics - Hilbert, Martin (Social Science Research Network, 2011)
The discussion about women’s access to and use of digital Information and Communication Technologies (ICT) in developing countries has been inconclusive so far. Some claim that women are rather technophobic and that men are much better users of digital tools, while others argue that women enthusiastically embrace digital communication. This article puts this question to an empirical test. We analyze data sets from 12 Latin American and 13 African countries from 2005-08. This is believed to be the most extensive empirical study in this field so far. The results are surprisingly consistent and revealing: the reason why fewer women access and use ICT is a direct result of their unfavorable conditions with respect to employment, education and income. When controlling for these variables, women turn out to be more active users of digital tools than men. This turns the alleged digital gender divide into an opportunity: given women’s affinity for ICT, and given that digital technologies are tools that can improve living conditions, ICT represent a concrete and tangible opportunity to tackle longstanding challenges of gender inequalities in developing countries, including access to employment, income, education and health services.
Keywords: Damned Lies; Digital Gender Divide or Technologically Empowered Women in Developing Countries? A Typical Case of Lies; Martin Hilbert; SSRN; and Statistics

Tiblo: a tangible learning aid for children with dyslexia - Pandey, Sumit; Srivastava, Swati (Association for Computing Machinery, 2011)
Dyslexia is a learning disability, which affects the ability to read and spell correctly. Special schools for children with dyslexia focus on individual growth, learning and psychological difficulties faced by the child. In this paper, we describe the design, development and testing of Tiblo (Tangible Interactive BLOcks), a tangible learning aid for children with dyslexia in the age group of 8 to 12 years. Tiblo has been specifically designed keeping in mind the psychological and emotional effects of dyslexia. We explain the process and results of an ethnographic study conducted at a school for children with dyslexia; the resulting concept development and prototyping. Further, we outline the testing process with the students at the school and the results of the same. The results showed that the children have a greater engagement in their classroom activities and there is an improvement in their retention abilities on using Tiblo. Also, they had a very strong sense of attachment and ownership towards the blocks and like to personalize it. This was in sharp contrast with other digital learning aids which offer a symptomatic and subject specific approach to aiding children with dyslexia and hence do not develop a personal one to one relationship with the child.
Keywords: collaborative learning; design case study; dyslexia; emotional design; interaction design; learning aids; play and learn; tangible user interfaces

Making mobile learning work: case studies of practice - Traxler, J.; Wishart, J. (Discussions in education, 2011)

Deliverology 101: A Field Guide For Educational Leaders - Barber, Michael; Moffit, Andy; Kihn, Paul (Corwin Press, 2011)
'Michael Barber's pioneering work as head of my Delivery Unit helped ensure real progress, not just with our education reforms, but with healthcare and policing too. It attracted worldwide attention. This guide distils the wisdom he gained at that time and has refined since. I strongly recommend it.' - Tony Blair, Former UK Prime Minister 1997-2007A step-by-step approach to delivering resultsMichael Barber, former chief advisor on delivery to British Prime Minister Tony Blair, and his colleagues Andy Moffit and Paul Kihn thoroughly describe Barber's proven reform delivery processes in this practical field guide. The timing is ideal, as Barack Obama's administration prioritizes education reform. Citing education reform case studies from more than 20 countries, the authors assert that most previous reforms were unsuccessful due to failed implementation. This book focuses on how to accomplish meaningful results, including:- Significant and ongoing education reform- Excellence and equity across public educationThe authors illustrate a field-tested program that ensures reform is achieved in the most profound sense, with students able to see, feel, and reap the benefits of a high-quality education. It is based not only on the experience of the Blair administration but also on case studies of successful implementation of reform in the U.S. and elsewhere.Listen as Barber describes the importance of the book:
Keywords: Education / Decision-Making & Problem Solving; Education / Leadership

Decentralisation policy and practice in Ghana: the promise and reality of community participation in education in rural communities - Essuman, Ato; Akyeampong, Kwame (Journal of Education Policy, 2011)
In 1987, the government of Ghana embarked on a process to decentralise education management to districts as part of wider social and democratic governance reforms. A central part of this reform was the prescription of active community participation in the affairs of schools within their locality. This paper explores the different meanings community participation had for school community stakeholders. It examines the multiple understandings of how community and school relations work and the factors which influence this relationship. Drawing on case study data, it argues that much of the theoretical and policy expectations on representation and participation in education by community members are only evident in form, but not as intended in practice. In poor rural contexts, it is often the local elite and relatively more educated members of the community, who become the new brokers of decision-making and, through their actions, close up the spaces for representation and participation by community members in the affairs of schools. Furthermore, the extent of community participation appears to be shaped by a ‘social contract’ based on the principle of reciprocity of roles between the community and schools, and that increasingly teachers feel accountable to the traditional hierarchical educational structure, and not to the community. The paper argues that the realisation of decentralisation policy in education has to contend with the realities of local politics of influence in the community, and tap into the positive side of this influence to improve education service delivery.
Keywords: Ghana; Parent Teacher Associations (PTA); School Management Committees (SMC); ___working_potential_duplicate; community participation; decentralisation policy